Pemeriksaan Sputum Basil Tahan Asam (BTA) pada Pasien Suspek Tuberculosis dengan Metode Ziehl Nelseen - Epsi Marwati; Oksita Asri Widyayanti; Suci Indah Budiarti; Delita Septining Tyas (Jurnal Nurse, 2021)
The infectious disease tuberculosis is transmitted through the air by Mycobacterium tuberculosis when an infected patient coughs, sneezes or talks. Indonesia is the third country among the countries that contribute to 60% of the world's TB cases. Diagnosis of TB can be done by detecting the presence of acid-fast bacilli (BTA) Mycobacterium tuberculosis in sputum examination. The Ziehl Neelsen method of BTA sputum examination has quite high sensitivity in detecting pulmonary TB. The aim of the study was to identify BTA sputum in patients with suspected pulmonary tuberculosis using the Ziehl Nelseen method. The research was carried out observationally through the BTA examination stage by taking sputum, laboratory checks and interpreting the results using the IUATED scale. The results of the BTA examination showed that patients who were positive for TB had positive BTA results at all three examination times. Acid-fast bacilli in TB positive patients are red after carbol fuchsin staining using the Ziehl Nelseen method. More male patients get TB than women, in this study, namely 33%. Patients who are positive for TB are aged 35 – 44 years. The conclusion of this study is the results of identification of BTA sputum from TB positive patients which shows a red color on carbol fuchsin staining using the Ziehl Nelseen method.